Trả lời:
![verified](https://1900.edu.vn/images/exam/verified.webp)
Giả sử Δx là số gia của đối số tại x0=1.
Ta có: Δy=f(1+Δx)−f(1)=√2(1+Δx)−1−1=2Δx√2Δx+1+1;
ΔyΔx=2ΔxΔx(√2Δx+1+1)=2√2Δx+1+1;
limΔx→0ΔyΔx=limΔx→02√2Δx+1+1=1 .
Vậy f'
Giả sử Δx là số gia của đối số tại x0=1.
Ta có: Δy=f(1+Δx)−f(1)=√2(1+Δx)−1−1=2Δx√2Δx+1+1;
ΔyΔx=2ΔxΔx(√2Δx+1+1)=2√2Δx+1+1;
limΔx→0ΔyΔx=limΔx→02√2Δx+1+1=1 .
Vậy f'
CÂU HỎI HOT CÙNG CHỦ ĐỀ
Câu 1:
Chứng minh rằng hàm số không có đạo hàm tại nhưng có đạo
hàm tại .
Chứng minh rằng hàm số không có đạo hàm tại nhưng có đạo
hàm tại .
Xem đáp án »
03/04/2024
114